2022
DOI: 10.3390/microorganisms10050897
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Lumpy Skin Disease in Myanmar and Molecular Analysis of the Field Virus Isolates

Abstract: Lumpy skin disease virus (LSDV) causes lumpy skin disease in cattle and buffaloes, which is associated with significant animal production and economic losses. Since the 2000s, LSDV has spread from Africa to several countries in the Middle East; Europe; and Asia; including, more recently, several south-east Asian countries. In November 2020, Myanmar reported its first LSD outbreak. This study reports on the first incursion of LSD in Myanmar and the molecular analysis of the LSDV detected. Staff from the Livesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 25 publications
(28 reference statements)
3
19
0
Order By: Relevance
“…LSD has been found in the Middle East since 2012 [ 9 ] and in Southeast Europe and North Caucasus since 2015 [ 10 , 11 ]. In 2019, the disease was identified in Bangladesh, India, and China before spreading to other regions of Asia including Vietnam and Myanmar in 2020 [ 12 , 13 , 14 , 15 , 16 ]. The disease is transmitted predominantly by bloodsucking insects such as stable flies, ticks, and mosquitoes [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…LSD has been found in the Middle East since 2012 [ 9 ] and in Southeast Europe and North Caucasus since 2015 [ 10 , 11 ]. In 2019, the disease was identified in Bangladesh, India, and China before spreading to other regions of Asia including Vietnam and Myanmar in 2020 [ 12 , 13 , 14 , 15 , 16 ]. The disease is transmitted predominantly by bloodsucking insects such as stable flies, ticks, and mosquitoes [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that LSDV isolates from outbreaks in some countries are genetically related [ 22 , 62 , 63 ]; therefore, international cooperation is critical to develop regional surveillance for monitoring, controlling, and preventing disease incursion. Such collaboration should also include sharing data regarding LSD outbreaks in each nation, such as epidemiological data and LSDV genetic information.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, numerous LSD outbreaks were found in southeast Europe. During 2019 to 2020, the disease became prevalent in many countries in Asia [ 20 , 21 , 22 , 23 , 24 , 25 ]. Currently, the disease is considered a major threat to the cattle industry and the livelihoods of cattle farmers in many regions of Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports based on EEV glycoprotein (LSD_126), RPO30, and GPCR (LSD_011) genes showed high similarity to Kenyan LSDV strains (Sudhakar et al, 2022). Identical to Indian strains, LSDV strains from Bangladesh (Badhy et al, 2021), Nepal (Koirala et al, 2022), and Myanmar (Maw et al, 2022), showed a high resemblance to Kenyan LSDV strains based on EEV glycoprotein, RPO30, and GPCR genes indicating the common source of infection through illegal trade of biologicals, animal products or animals. LSDV strains from Vietnam, Thailand, China, and Russia are not related to Kenyan strains but instead are recombinant strains.…”
Section: Comparison With Other Lsdv Gtpv and Sppv Genomesmentioning
confidence: 99%
“…The disease was originally described in Zambia in 1929, later spreading to South Africa and Kenya. Initially, the disease was contained to Africa and the Middle East (Davies, 1982), later spreading to Europe followed by outbreaks in several Asian countries including India (Sudhakar et al, 2019), Nepal (Acharya and Subedi, 2020), Bangladesh (Hasib et al, 2021), Vietnam (Tran et al, 2021), Thailand (Arjkumpa et al, 2021), Myanmar (Maw et al, 2022), China (Lu et al, 2021), and Hongkong (Flannery et al, 2021) has raised serious concerns. The clinical manifestations of lumpy skin disease include pyrexia, characteristic nodules on different body parts, lymphadenopathy, drop in milk production, weight loss, infertility, abortion, and sometimes death (Tuppurainen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%